2004
DOI: 10.1111/j.0022-202x.2004.22533.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-Induced Melanogenesis Shows Differences in Morphologic and Melanogenic Preferences of Melanosomes from Light and Dark Skin Types

Abstract: The quality, quantity and distribution of melanosomes in epidermis play a crucial role in the determination of skin color and its sensitivity to UV radiation. Melanocyte cultures originating from individuals with light and dark skin types were grown in media with varying concentration of L-tyrosine. Melanosomal melanin content and the size of the organelles were measured after subcellular fractionation. In light-skin type cells, increased melanin production resulted in a more elliptical shape of melanosomes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…2). This observation agrees with human physiology, since melanin is produced by melanocytes in the skin, meninges, and CP [13] in both B/AA and W individuals, but to a greater extent in B/AA individuals [37]. However, high CP SUVR in light-skinned individuals could also point to additional factors contributing to CP FTP signal, which may include both off-target binding (e.g., iron deposits, Biondi rings, calcifications/mineralizations, MAO-A) and on-target binding (as observed within CP epithelial cells by Ikonomovic and colleagues) [38].…”
Section: Discussionsupporting
confidence: 84%
“…2). This observation agrees with human physiology, since melanin is produced by melanocytes in the skin, meninges, and CP [13] in both B/AA and W individuals, but to a greater extent in B/AA individuals [37]. However, high CP SUVR in light-skinned individuals could also point to additional factors contributing to CP FTP signal, which may include both off-target binding (e.g., iron deposits, Biondi rings, calcifications/mineralizations, MAO-A) and on-target binding (as observed within CP epithelial cells by Ikonomovic and colleagues) [38].…”
Section: Discussionsupporting
confidence: 84%
“…Regardless of the underlying mechanism, reduced glutathione concentration increases the risk of oxidative damage in these cells. Pigment cells with stimulated production of pheomelanin (26) are the best candidates for such increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Dark pigment, eumelanin, protects skin cells from UV damage (50). In contrast, the yellow-red-colored pheomelanin is less effective in providing UV protection (51). Recently, Mitra et al have shown that pheomelanin may even promote oxidative DNA injury by generating free radicals in the absence of UV in fair skin individual (52).…”
Section: Memory Cla+ T Cells In Msmentioning
confidence: 99%